2021
DOI: 10.1186/s13073-021-00878-y
|View full text |Cite
|
Sign up to set email alerts
|

Emerging genetic complexity and rare genetic variants in neurodegenerative brain diseases

Abstract: Knowledge of the molecular etiology of neurodegenerative brain diseases (NBD) has substantially increased over the past three decades. Early genetic studies of NBD families identified rare and highly penetrant deleterious mutations in causal genes that segregate with disease. Large genome-wide association studies uncovered common genetic variants that influenced disease risk. Major developments in next-generation sequencing (NGS) technologies accelerated gene discoveries at an unprecedented rate and revealed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 116 publications
0
15
0
Order By: Relevance
“…It was suggested that KCNB2 was one of the genes with the most significant copy number gains in ALS ( Morello et al, 2018 ). KCNS3 was reported to be upregulated in early pathological stages of AD ( Saura et al, 2015 ), and as a risk gene in PD ( Perrone et al, 2021 ). Administration of 4-Aminopyridine, a non-selective blocker of Kv channels, restored ion channel dynamics, rescued neuronal activity, and relieved ER stress in ALS MNs ( Naujock et al, 2016 ), reinforcing our hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that KCNB2 was one of the genes with the most significant copy number gains in ALS ( Morello et al, 2018 ). KCNS3 was reported to be upregulated in early pathological stages of AD ( Saura et al, 2015 ), and as a risk gene in PD ( Perrone et al, 2021 ). Administration of 4-Aminopyridine, a non-selective blocker of Kv channels, restored ion channel dynamics, rescued neuronal activity, and relieved ER stress in ALS MNs ( Naujock et al, 2016 ), reinforcing our hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Neurodegeneration is a progressive and non-reversable process affecting the physiology of CNS and/or PNS plasticity [ 94 , 95 ]. These diseases are mainly linked to genetic mutations, which eventually manifest as pathological when affecting new protein synthesis and homeostasis [ 95 , 96 ].…”
Section: Neurodegenerative Diseases: Is There a Lesson To Learn From Development?mentioning
confidence: 99%
“…Proteostasis disruption has serious consequences such as the pathogenesis of a variety of disorders, including NDs, ageing and cancer [18][19][20]. Additionally, mutations in genes encoding pathogenic proteins can cause misfolding and sequential aggregation in NDs [21]. The proteostasis network can clear aggregated proteins in the absence of gene mutations; however, this capacity declines with age, resulting in proteostasis dysfunction [22].…”
Section: Introductionmentioning
confidence: 99%